Implementasi Kebijakan Pelayanan Kesehatan Masyarakat Di Puskesmas Gorua Kecamatan Tobelo Utara Kebupaten Halmahera Utara - Paliema, Anita; Rumapea, Patar (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: The evidence suggests also that Gorua health centers still lack the human resources in this casemedical personnel. This study uses qualitative methods. Data were collected through interviews and observation techniques. Interviews were conducted at 45 of the informant elements service providers and service recipients. This study consists of four dimensions, namely communication, resources, disposition, and organizational structure / bureaucracy, it turns out that the low isindicated that human resource dimensions Goruahealth centers still lack themedicalpersonnel. The conclusion that can be drawn from these resultsis that in general, the implementation of public health care policy in health centers Tobelo Gorua Northern District high enough, but not obtimal. This is due to that health center Gorua There are still limitations, namely in terms of the human resources of medical personnel(doctor). Generallyrecommendedadviceto the Government of North Halmahera in order to make Government Area of the health services. And in accordance with 4 (four) Indicator research problems. The government is expected to improve themanagement of public services provision of Human Resources (HR) in this case themedical personnel who considered capable of providing anytindakkanin accordance with the competencyowned. Keywords: Public Health Service, Policy Implementation Gorua Health Center